HLA-B*58:01 for Allopurinol-Induced Cutaneous Adverse Drug Reactions: Implication for Clinical Interpretation in Thailand - Sukasem, Chonlaphat; Jantararoungtong, Thawinee; Kuntawong, Parnrat; Puangpetch, Apichaya; Koomdee, Napatrupron; Satapornpong, Patompong; Supapsophon, Patcharin; Klaewsongkram, Jettanong; Rerkpattanapipat, Ticha (Frontiers in Pharmacology, 2016)
Abstract Background: The aim of this study was to investigate the predisposition to different types of allopurinol-induced cutaneous adverse drug reactions (CADR), including Stevens-Johnson syndrome (SJS), toxic epidermal necrolysis (TEN) (SJS-TEN, n=13), drug reaction with eosinophilia and systemic symptoms (DRESS, n=10) and severe Maculopapular eruption (MPE) (n=7), conferred by HLA-B*58:01 in a Thai population. METHODS: This case-controlled association study compares 30 patients with allopurinol-induced CADR, allopurinol-tolerant control patients (n=100) and a Thai general population (n=1,095). Patients’ human leukocyte antigen type B (HLA-B) alleles were genotyped by using a two-stage sequence-specific oligonucleotide probe system. RESULTS: Of a total 30 patients with CADR due to allopurinol, 29 (96.7%) patients were found to be at least heterozygous for HLA-B*58:01, while was found only 4.0% in allopurinol-tolerant patients (p<0.001). Odds ratio (OR) for the association of HLA-B*58:01 with allopurinol-induced CADR in this population was 696.0 (95% CI: 74.8-6475.0). The HLA-B*58:01 allele was present in all patients with allopurinol-induced SJS-TEN (OR=579.0, 95%CI: 29.5-11362.7, p<0.001) and DRESS (OR 430.3, 95%CI: 22.6-8958.9, p<0.001). Additionally, OR of HLA-B*58:01 was highly significant in the allopurinol-induced MPE patients (OR 144.0, 95%CI: 13.9-1497.0, p<0.001), CONCLUSION: In this study we confirmed the association between HLAB*58:01 and allopurinol-induced SJS-TEN in a Thai population. In addition, we identified an association between HLA-B*58:01 and allopurinol-induced DRESS and MPE in this population. Therefore, HLA-B*58:01 can be used as a pharmacogenetic marker for allopurinol-induced CADR including SJS-TEN, DRESS and MPE. These results suggest that screening for HLA-B*58:01 alleles in patients who will be treated with allopurinol would be clinically helpful in preventing the risk of developing CADR in a Thai patients.